Inovasi Nugget Jagung dengan Memanfaatkan Hasil Panen Tanaman Jagung di Desa Balongwono oleh Mahasiswa KKNT Bela Negara UPN “Veteran” Jawa Timur - Vynka Zahira Sausan; Intan Mitayani; Safira Salma Azzahra; Hendra Maulana (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Balongwono Village has the potential of natural resources that are very dominant, namely corn agricultural products and some of the Balongwono Village people make a living as corn farmers. The purpose of the socialization carried out by group 1 KKNT Bela Negara UPN "Veteran" East Java is to increase public knowledge about the use of corn and utilize corn to be more effective, innovative, and efficient which can be traded and can improve the economy of housewives in Balongwono Village. It is hoped that with this socialization activity, this "Corn Chick" corn nugget can become a superior innovation product that has high selling value. The method used is The method of implementation in the innovation activity of utilizing natural resources in the form of corn is carried out by learning by doing, the first stage is sharing recipes, the second is sharing knowledge by explaining the ingredients used and the process of making products, the tools needed, how to store and serve, finally student group 1 demonstrates how to process the product. The results of this service are that students have succeeded in socializing the use of corn and participants can absorb the knowledge that has been given.